THE UTILIZATION OF BAGASSE AND LOGGING RESIDUES OF EUCALYPTUS FOR PARTICLEBOARD PRODUCTION - Hossein Hosseinkhani; Abdolrahman Hosseinzadeh; Fardad Golbabaei; Amir Nourbakhsh; Nayeralsadat Sadraei; masoudreza Habibi (تحقیقات علوم چوب و کاغذ ایران, 2000)
In this study, the effect of board type, press time and resin content on the strength of particleboard have been evaluated. The boards made for this study contained bagasse and logging residues of Eucalyptus wood particles at a 50 to 50 ratio and employed Urea formaldehyde (UF) resin as the binder. Variable factors are as follows:- type of board; single layer, three layer- press time; 5 , 6 , 7 , minutes- resin content; 9 , 10 , 11 percentThree boards' were manufactured for each combination of variables. Samples of all the boards made were tested by the methods described in DIN 68763 standard to obtain mean values of bending strength, and internal bond strength (LB). In addition samples of each type of board were tested for thickness swelling after immersion in water for 2 hours and 24 hours respectively.The results of this study show clearly that three layer particleboard has significantly higher bending strength than single layer, but single layer boards have better properties from the physical aspect. Increasing the content of U.F resin from 9 per cent to 10 per cent was found to reduce the thickness swelling, and tended to improve the strength properties of the board, in both single layer and three layer boards. Press time has significant effect on bending strength and I.B Highest MOR and MOE were observed on three layer board pressed for 7 minutes.